First high-quality genome assembly data of sago palm (Metroxylon sagu Rottboll) - Whye, Leonard Kit Lim; Mei, Melinda Lin Lau; Chung, Hung Hui; Hasnain, Hussain; Han, Ming Gan (Elsevier Inc., 2022)
The sago palm (Metroxylon sagu Rottboll) is a tropical halophytic starch-producing, economically important crop palm mainly located in Southeast Asian countries. Recently, a genome survey was conducted on this palm using the Illumina sequencing platform, with a very low (21.5%) BUSCO genome completeness score, and most of them (∼78%) are either fragmented or missing. Thus, in this study, the sago palm genome completeness was further improved with the utilization of the Nanopore sequencing platform that produced longer reads. A hybrid genome assembly was conducted, and the outcome was a much complete sago palm genome with BUSCO completeness achieved at as high as 97.9%, with only ∼2% of them either fragmented or missing. The estimated genome size of the sago palm is 509,812,790 bp in this study. A sum of 33,242 protein-coding genes was revealed from the sago palm genome and around 96.39% of them had been functionally annotated. An investigation on the carbohydrate metabolism KEGG pathways also unearthed that starch synthesis was one of the major sago palm activities. The genome data obtained from this work is indispensable for future molecular evolutionary and genome-wide association studies on the economically important sago palm.